Presentation: Forty Years of Allpanchis - Valle Rondón, Fernando (2009)
Allpanchis magazine turns forty years old, a true milestone for a periodic publication that with great perseverance has been offering, in its 74 issues, studies that address the Andean reality from various disciplines, academic currents and perspectives. Throughout these years, the journal has published 691 collaborations by some five hundred authors, with a plurality of specialties —such as Anthropology, History, Sociology or Religious Sciences— that express well its multidisciplinary nature. For all these reasons, we present a commemorative double issue in this edition.